The EU's enlargement and NATO's prospects in the context of the war and post-war political dynamics - Valentin Naumescu (Eastern Journal of European Studies)
Combining EU and NATO analyses is useful for projecting an integrated vision for the future of Europe. The topic of a new EU enlargement got political momentum after 2022, more than 20 years after the previous wave of optimism and interest for the post-communist Central and Eastern European countries. The Russian invasion of Ukraine is certainly the main reason of this renewed interest. The European Council of mid-December 2023 decided to open the negotiations for EU accession with two new candidates, Ukraine and the Republic of Moldova, marking this way a historic shift of the EU enlargement policy in relation to the post-Soviet republics, after the accession of the Baltic States in 2004. This research explores the turbulent context in which both the EU and NATO should shape their convergent perspectives for the next institutional reforms, not only limited to enlargement(s) but also regarding the new (external as well as internal) contestations and revisionism. The article also deals with the major challenges of the international security context and addresses an essential question - Does Europe need a Plan B?